Hesychast Concept in the Iconographic Programme of the Frescoes in the Church of Assumption in Melyotovo - Freze, Anna A. (Actual Problems of Theory and History of Art, 2025)
One of the main themes of the frescoes’ iconographic program in the church of the Assumption of the Virgin in Melyotovo (1465) is the reflection of the hesychastic tradition ideas, such as Divine energies, the uncreated Light and their influence on a saint. The following frescoes highlight these conceptions: Virgin of the Burning Bush with two figures of Moses performing miracles with his staff; Jesus Christ bringing judicious robber to Heaven; six figures of monks in the diaconicon; Jesus Christ — Sun of Justice.
Keywords: Pskov; 15th century; hesychasm; frescoes; iconography